DVR with Modified Y Source Inverter and MCFC - Chakravorty, J.; Sharma, G. (Engineering, Technology & Applied Science Research, 2019)
Power quality is a big challenge nowadays. Various disturbances present in the power system are voltage sag, voltage swell, harmonics, transients, interruptions, voltage collapse etc. To solve the problem of power quality, various custom power devices are generally used in a power system, dynamic voltage restorer (DVR) being one of them. DVR is used for the compensation of voltage sag and swell. In this paper, a model of DVR with molten carbonate fuel cell (MCFC) and Y source inverter is proposed. The proposed model is compared with the existing ones to check its performance characteristics. MATLAB/SIMULINK was been used to check and compare the performance of the proposed with existing models.